Neuroprotective effects of resistance physical exercise on the APP/PS1 mouse model of Alzheimer’s disease - Campos, Henrique Correia; Ribeiro, Deidiane Elisa; Hashiguchi, Debora; Glaser, Talita; Milanis, Milena da Silva; Gimenes, Christiane; Suchecki, Deborah; Arida, Ricardo Mario; Ulrich, Henning; Monteiro Longo, Beatriz (Frontiers in Neuroscience, 2023)
Physical exercise has neuroprotective effects often associated with the control of inflammatory responses in Alzheimer´s disease (AD). However, different from aerobic exercise, only few studies have investigated the effects of resistance exercise (RE). The double-transgenic APPswe/PS1dE9 (APP/PS1) mice exhibit increased levels of hippocampal amyloid-β (Αβ) plaques, hyperlocomotion, cognitive deficits and exacerbated inflammatory response. Therefore, this study aimed to investigate the effect of RE training in the prevention of these AD-related alterations in APP/PS1. For this, 6–7 months old male APP/PS1 transgenic mice and their littermates, negative for the mutations (CTRL), were distributed into three groups: CTRL, APP/PS1, APP/PS1+RE. One day after the last exercise training session, mice were exposed to the open field test. Twenty-four hours later, the novel object recognition test was performed followed by quantification of of hippocampal Aβ protein, microglia cells and plasma corticosterone concentration. We observed that, compared to the non-mutant littermates, APPswe/PS1dE9 transgenic mice showed increased hippocampal Aβ plaques and higher plasma corticosterone levels, increased locomotion and diminished central crossings in the open field test. Despite these alterations, 6-7 months-old APP/PS1 mice presented no memory impairment in the novel object recognition test compared to CTRL animals, which is accordance to previous studies. We have shown for the first time that RE normalized to CTRL levels these behavioral and molecular alterations. In addition, the RE protocol increased the number of microglia cells in the hippocampus of APP/PS1 mice. Altogether, this study highlights the beneficial effects of RE training as a complementary treatment of AD.